PPI in preventing gastrointestinal injury in minor ischemic stroke or TIA patients at low risk of gastrointestinal bleeding treated with short-term dual antiplatelet therapy - Cao, Lu; Quan, Kejia; Zhang, Dan; Li, Rui; Zhou, Nan; Zhang, Peng (Frontiers in Pharmacology, 2025)
ObjectiveTo analyse the use of prophylactic proton pump inhibitors (PPIs) and their benefits for the prevention of gastrointestinal injury and to determine the optimal course of preventive use among patients with minor ischaemic stroke (IS) and transient ischaemic attack (TIA) at low risk of gastrointestinal bleeding (GIB) treated with short-term dual-antiplatelet therapy (DAPT).MethodsWe retrospectively collected clinical data from the hospital information system (HIS) from January 2022 to December 2023. The data were collected from patients who were admitted to a tertiary hospital with a first occurrence of minor IS/TIA diagnosed within 14 days and treated with short-term DAPT. Univariate and multivariate logistic regression analyses were used to explore the correlations between the use of PPIs, different treatment durations, and the incidence rates of GIB, gastrointestinal discomfort, other types of bleeding, and pneumonia in these patients.ResultsA total of 220 patients were included, with 52 in the PPI group (23.64%) and 168 in the non-PPI group (76.36%). The results showed that PPI use did not significantly reduce the incidence of GIB (P = 0.059) or other types of bleeding (P = 0.916) in patients who were treated with DAPT and were at low risk of GIB. The incidence of pneumonia in the PPI group was higher than that in the non-PPI group, but the difference was not statistically significant (42.86% vs. 23.00%, P = 0.840). However, PPI use significantly reduced the occurrence of gastrointestinal discomfort (P = 0.033, OR: 0.448; 95% CI: 0.215–0.935), with no significant difference based on treatment duration (≤7 days vs. >7 days, P = 0.520).ConclusionRegular use of PPIs within the first 7 days of initiating DAPT in patients with minor IS/TIA at low risk of GIB significantly reduces symptoms of gastrointestinal discomfort while minimizing adverse effects due to overuse of PPIs.